DESIGNING AND IMPLEMENTATING A CORRELATION COMPENSATOR FOR THE TARGET DETECTING SYSTEM IN CONTROLLED FLYING VEHICLE - Hiền (Journal of Military Science and Technology, 2021)
The paper is the result of research in the field of signal processing with active jamming for detecting system in passive detector. The paper presents basic theory, analysis of the receiver structure, signal characteristics, block diagram, structure diagram and operation principle of the correlation compensator in the detecting system. It also describes a mathematical model to implement Correlative compensation algorithm. The simulation results, performed in Matlab/Simulink and Proteus environments, show the consistency between mathematical model and circuit. That is the basis for practical design of correlation compensator for target detecting system.